Critical Thinking within the Context of the Revised Bloom’s Taxonomy in Written Language Tests - Yulis Setyowati; Susanto Susanto; Ahmad Munir (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Critical thinking is still infrequently taught in the classroom, particularly in Indonesia, despite the fact that many experts believe it is a vital problem in the education area. As a result, the purpose of this research was to picture the use of the revised Bloom taxonomy to investigate critical thinking in language tests. The article analyses the test items in language tests which consists of the High thinking order level based on the revised Bloom's theory. To begin, this current work summarizes past research, which found that critical thinking has been studied in a variety of areas in language teaching but has yet to address language evaluation using the revised Bloom's taxonomy. It is necessary to present the six-level Anderson and Krathwohl (2001) taxonomy, which is then referred to as the revised Bloom's taxonomy, before discussing how to promote critical thinking. Then, the finding indicates that the item tests which are considered to be high order skills consistently direct students to think critically and systematically.